A Multi-level, Multi-platform Approach to Communications on the South West Hub CCS Project. (July 2017) - Ferguson, Beth; Van Gent, Dominique
Abstract: The multiple levels of engagement required for any project operating on individual landholders' properties and within a broader community necessitate some ranking of stakeholders. Add to this the various tools and forums that represent a multi-platform delivery utilised across the engagement level spectrum, and you have a complex and variable approach to communications. The South West Hub's (SW Hub) challenge is to appropriately engage with those many and varied stakeholders in a manner that is inclusive, relevant and responsive. The SW Hub operates within the Western Australian Government's Department of Mines and Petroleum (DMP). A key strategic outcome for DMP is the provision of a proactive and targeted engagement that is valued by stakeholders and improves the outcomes delivered. A priority contribution to achieving that outcome is the development of communication and engagement plans that are specific to stakeholder needs. With the SW Hub looking more and more like an opportunity for the geological storage of industrially generated CO2 in Western Australia, the need to keep the community and other stakeholders informed and engaged is, and remains, paramount. This paper explores the SW Hub's communications strategy which, between 2011 and 2016, has focused on familiarisation and education across formal and informal, general and highly technical platforms, with a view to normalising Carbon Capture and Storage (CCS) and therefore contributing to gaining community acceptance of the concept.